2009
DOI: 10.1002/ps.1886
|View full text |Cite
|
Sign up to set email alerts
|

Species determination of Malaysian Bactrocera pests using PCR‐RFLP analyses (Diptera: Tephritidae)

Abstract: PCR-RFLP analyses are able to identify positively five Bactrocera species, while B. papayae and B. carambolae might possibly be separated from one another, even if immature life stages or adult body parts are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…; Chua et al . ). These pests have directly caused defects to carambola and have reduced the quality of the fruits, thus causing economic loss.…”
Section: Introductionmentioning
confidence: 97%
“…; Chua et al . ). These pests have directly caused defects to carambola and have reduced the quality of the fruits, thus causing economic loss.…”
Section: Introductionmentioning
confidence: 97%
“…An ongoing research effort is being directed towards resolving the biological relationships among these taxonomically challenging species, with some publications finding no difference between them (Tan et al , 2011), and others finding subtle morphological differences (Drew et al , 2008). Recent molecular phylogenies and species‐level barcoding studies consistently suggest that these taxa are very close genetically (Armstrong & Ball, 2005; Chua et al , 2010; Krosch et al , 2012). However, it is still unclear from the literature whether, where such differences are found, these equate to interspecific or intraspecific variation (Schutze et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, comparison information can be made by looking at BLAST analysis and the construction of MP and BI trees has given more advantages to discriminate between closely related species. Bactrocera species also were confirmed using COI gene which has been extensively used in most identification of these species [18]. This study indicated that B. papayae and B. carambolae have infested wide variety of crops including star fruits, guavas and wax apples.…”
Section: Discussionmentioning
confidence: 62%